Enhancing Arabic Speaking Skills in Traditional Pesantren - Ahmad Maghfurin; Moh. Ahsanul Husna; Nur Cholid; Nurul Asma Mazlan; Jumiati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Proficiency in the Arabic language is imperative in the context of Islamic education. However, the effective study of Arabic remains a challenge, hindering students' abilities to engage with Islamic texts and communicate in Arabic-speaking environments. Focusing on Pesantren Raudhatul Ulum-Pati, this study investigates the strategies and challenges associated with enhancing Arabic speaking skills in traditional Islamic boarding schools (Pesantren). Specific teaching techniques employed by instructors at this pesantren, aimed at improving students' Arabic speaking abilities, as well as the challenges impeding fluency, were examined through a qualitative research design, including classroom observations and interviews with teachers, administrators, and students. The outcomes highlight the importance of innovative methods and shed light on issues such as a lack of exposure to Arabic-speaking environments. The program implemented in this pesantren serves as an exemplary model for other traditional Islamic boarding schools seeking to elevate their students' proficiency in the Arabic language. The findings of this study hold significant implications for all traditional Islamic boarding schools (pesantren) in Indonesia.